Natural Alternatives against Bacterial Foodborne Pathogens - Martinez-Rodriguez, Adolfo J.; Silvan, Jose Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The dramatic increase in resistance to antibiotics and disinfectants of foodborne bacterial pathogens has become a serious health problem for consumers and a growing concern for food safety authorities. In this situation, new strategies are being explored that can be employed as useful alternatives in the fight against these pathogens. Natural compounds are considered among the most promising candidates due to their high acceptability and low levels of toxicity, contributing to increased environmental sustainability. Many of these compounds have different bioactive properties and can act as antimicrobials and/or anti-inflammatories, also showing the ability to inhibit the formation of bacterial biofilms. In this book, the invited authors provide evidence that contributes to the visibility of some of these new antibacterial agents, presenting different strategies potentially applicable in the control of various foodborne pathogens.